Bit-plane Oriented Image Encryption through Prime-Nonprime based Positional Substitution (BPIEPNPS) - Dasgupta, Madhuchhanda; Mandal, JK (International Journal of Computer Sciences and Engineering, 2025)
In this paper a bit-plane based novel image encryption technique has been proposed using pixel shuffling based on characteristics of bit position within a pixel. The image is decomposed into eight binary bit-planes and all the bit-planes are scrambled using Recursive Positional Substitution based on Prime - Nonprime method. The performance of the algorithm is a discussed against common attacks like brute force attack, cipher related attacks and Differential attacks. Test through histogram analysis, correlation co-efficient analysis are provided in simulations and security analysis to shows enhanced performance of the proposed algorithm.